Effect of preconditioning of human umbilical cord mesenchymal stem cells with hydrogen peroxide on the therapeutic potential of MSCs in the cyclophosphamide -induced premature ovarian failure mice model - Ladan Jalali; Azra Allahveisie; Shohreh Rezaei; Leila Ravanyar; Jafar Kiasatfar; Mohammad-Jafar Rezaie; Amir Raoofi (Elsevier, 2023)
Objective: Exposure of stem cells to sublethal levels of hydrogen peroxide (H2O2) can prevent oxidative stress-induced apoptosis. In the present study, the effects of H2O2 preconditioning on the therapeutic potential of human umbilical vein cord mesenchymal stem cells (hUCV-MSCs) were evaluated in a murine model of premature ovarian failure. Materials and methods: Mature mice were divided into 4 groups, and 10 mice were incorporated into each group. The control (Ctrl) group received phosphate buffered saline (PBS) intraperitoneal (IP), and the CTX group was injected IP with cyclophosphamide (CTX). The CTX + MSC group after receiving CTX was injected with a single dose of hUCV-MSCs labeled with CM-DiI intravenously (IV), whereas the CTX + preMSCs group after CTX injection received preconditioned MSCs with H2O2 IV. Seven days later, the mice were euthanized, and their ovaries were removed for histological studies such as H&E staining and the TUNEL assay. Furthermore, the numbers of CM-DiI-labeled hUCV-MSCs in the different regions of the ovary were calculated. FSH and estradiol values in the serum were measured. Results: Our studies showed that CTX caused degenerative changes and follicular loss in the ovary. The number of follicles in the CTX + MSCs and CTX + PreMSCs groups was significantly higher compared to the CTX group. In addition, in the CTX + PreMSCs group, the numbers of different types of follicles were higher than in the CTX-MSC group. Immunohistochemical studies in the CTX + MSCs and CTX + PreMSCs groups showed little evidence of TUNEL positivity compared with the CTX group. Moreover, the apoptotic index decreased in the CTX + PreMSCs group compared to the CTX + MSCs group. Moreover, CM-DiI-labeled MSCs in the ovary in the CTX + pre-MSCs group were higher than in the CTX + MSCs group. Conclusion: Our experiment offers preconditioning as an effective strategy in stem cell therapy to potentiate MSCs' therapeutic efficacy in ovarian function failure.